2019
DOI: 10.1038/s41467-019-11540-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated TORC1 and PKA signaling control the temporal activation of glucose-induced gene expression in yeast

Abstract: The growth rate of a yeast cell is controlled by the target of rapamycin kinase complex I (TORC1) and cAMP-dependent protein kinase (PKA) pathways. To determine how TORC1 and PKA cooperate to regulate cell growth, we performed temporal analysis of gene expression in yeast switched from a non-fermentable substrate, to glucose, in the presence and absence of TORC1 and PKA inhibitors. Quantitative analysis of these data reveals that PKA drives the expression of key cell growth genes during transitions into, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 53 publications
5
79
0
1
Order By: Relevance
“…However, the tor1 mutant is more likely to acquire adaptive mutations in the RAS/PKA pathway (6 out of 21 multihits in tor1, 1 out of 19 in cyr1, 0 out of 5 in gpb2), while cyr1 and gpb2 mutants are more likely to acquire mutations in the TOR/Sch9 pathway (1 out of 19 in cyr1, 2 out of 5 in gpb2, 0 out of 21 in tor1). The observation that double mutants on the RAS/PKA and TOR/Sch9 pathways are more fit than their corresponding single mutants and were selected for, whereas double mutants on the same pathway were not, suggests that the TOR and RAS/PKA pathways are not redundant in how they increase fitness, as has been previously shown 51 .…”
Section: Molecular Targets Of Adaptation Are Contingent Upon the Founmentioning
confidence: 54%
“…However, the tor1 mutant is more likely to acquire adaptive mutations in the RAS/PKA pathway (6 out of 21 multihits in tor1, 1 out of 19 in cyr1, 0 out of 5 in gpb2), while cyr1 and gpb2 mutants are more likely to acquire mutations in the TOR/Sch9 pathway (1 out of 19 in cyr1, 2 out of 5 in gpb2, 0 out of 21 in tor1). The observation that double mutants on the RAS/PKA and TOR/Sch9 pathways are more fit than their corresponding single mutants and were selected for, whereas double mutants on the same pathway were not, suggests that the TOR and RAS/PKA pathways are not redundant in how they increase fitness, as has been previously shown 51 .…”
Section: Molecular Targets Of Adaptation Are Contingent Upon the Founmentioning
confidence: 54%
“…A recent study evaluated the contributions of PKA and TORC1 to transcriptional regulation of ribosomal biogenesis and protein synthesis genes following transfer of cells from a non-fermentable carbon source to glucose using chemical inhibitors (31). They found that while PKA was required for the regulation of ribosomal biogenesis/ protein synthesis genes during transition into glucose-containing medium, TORC1 was required for their steady state gene expression (31). Although they proposed that TORC1 regulates the ribosomal biogenesis genes by inactivating transcriptional repressors Dot6 and Tod6 via Sch9, rapamycin treatment affected the gene expression in a dot6Δ tod6Δ strain (31).…”
Section: Discussionmentioning
confidence: 99%
“…They found that while PKA was required for the regulation of ribosomal biogenesis/ protein synthesis genes during transition into glucose-containing medium, TORC1 was required for their steady state gene expression (31). Although they proposed that TORC1 regulates the ribosomal biogenesis genes by inactivating transcriptional repressors Dot6 and Tod6 via Sch9, rapamycin treatment affected the gene expression in a dot6Δ tod6Δ strain (31). This is consistent with our observations that rapamycin treatment affected the expression of the TGC genes in the sch9Δ strain ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The desire to control the important aspects of our lives is common, and it may be rooted in nature [16]. In this paper, we address one aspect that is becoming increasingly important, namely online privacy regarding the disclosure of personal information.…”
Section: Introductionmentioning
confidence: 99%